Analisis Sistem Penggajian Karyawan Panen di Perkebunan Kelapa Sawit - Muhammad Sapruwan (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Payroll system for employees are generally calculated on the basis of attendance or working day (WD) and other income such as overtime pay, benefit and penalty. In general, salary payroll in palm oil plantation is known as a whole base system. The purpose of this study was to know about the payroll system for harvesting employees, especially free daily employees (FDE) in palm oil plantation. This research uses qualitative analysis approach with quantitative descriptive analysis method, that is describe the real condition of payroll system based on the performance of harvesting employees, especially FDE. The result show that in general, the payroll system for harvesting employees in palm oil plantation uses the Piecework method, which is a payroll system based on the output of fresh fruit bunches (FFB). The calculations include: whole base, overall-finished incentive, over-base incentive and penalty. The salary calculation for harvesting employees whose performance is over-base is salary + overall-finished incentive + harvest incentive – penalty, while for employees whose performance is under-base is proportional salary (the number of harvested bunches divided by the number of basic bunches multiplied by 1 (one) WD is multiplied district minimum salery (DMS).